Prospects For the Cultivation of Citrus (Lemon - Meyer, Orange, Mandarin, Grapefruit) Fruits in The Greenhouses of The Book District - Ergasheva Nigora G'ayratovna (Zien Journals, 2023)
This article provides feedback on the prospects for the cultivation of citrus fruits in the greenhouses of Kitobtumani and recommendations on the cultivation of citrus fruits.
Keywords: citrus fruit; greenhouse; lemon; Orange